Chinese Aesthetic Mask: Three Forehead and Five Eyes—Holistic Processing and Facial Attractiveness. (June 2021) - Lin, Jia; Zhou, Guomei
Human face processing has been attributed to holistic processing. Here, we ask whether humans are sensitive to configural information when perceiving facial attractiveness. By referring to a traditional Chinese aesthetic theory—Three Forehead and Five Eyes—we generated a series of faces that differed in spacing between facial features. We adopted a two-alternative forced-choice task in Experiment 1 and a rating task in Experiment 2 to assess attractiveness. Both tasks showed a consistent result: The faces which fit the Chinese aesthetic theory were chosen or rated as most attractive. This effect of configural information on facial attractiveness was larger for faces with highly attractive features than for faces with low attractive features. These findings provide experimental evidence for the traditional Chinese aesthetic theory. This issue can be further explored from the perspective of culture in the future.